EFFECT ANALYSIS OF TRUST, EASE, INFORMATION QUALITY, HALAL PRODUCT ON ONLINE PURCHASE DECISION OF 2016-2018 BATCH STUDENTS OF ISLAMIC ECONOMICS STUDY PROGRAM IN UIN WALISONGO AT SHOPEE MARKETPLACE - Fataron, Zuhdan Ady; Rohmah, Hariyanti (Journal of Digital Marketing and Halal Industry, 2019)
The existence of onlineshop has many advantages, one of them is to facilitate the effective purchase and selling for the community. Shopee is an online shop platform that has many users. It can not be separated from the trust built by the marketplace. Trust, ease, and quality of information become important aspects for marketplaces to attract customer interest. Halal products are special requirements given to customers who are Muslim, in order to avoid things that are prohibited by syara 'against purchase decisions in the marketplace. To see the effect, a research was conducted on students as the biggest onlineshop actors with variables of trust, ease, quality of information and halal products as independent variables on purchase decisions as dependent variable. The results showed that the variables of trust, ease, quality of information and halal products had a positive and significant effect on purchase decisions in shopee marketplace.